Transcranial Direct Current Stimulation in Obsessive-Compulsive Disorder, Posttraumatic Stress Disorder, and Anxiety Disorders. Issue 3 (September 2018) - D'Urso, Giordano; Mantovani, Antonio; Patti, Sara; Toscano, Elena; de Bartolomeis, Andrea
Abstract : Abstract: Obsessive-compulsive disorder (OCD), posttraumatic stress disorder (PTSD), and anxiety disorders share the basic clinical feature of anxiety, which probably explains their common response to similar pharmacological and psychological interventions. Transcranial direct current stimulation (tDCS) is a neuromodulation technique that has proved effective in reducing the symptoms of a number of neuropsychiatric disorders. It was also used in healthy subjects to modulate neuropsychological processes that are involved in the pathophysiology of anxiety. We review the published studies in which tDCS was administered to patients with OCD, PTSD, or anxiety disorders. Our systematic search in the major electronic databases resulted in 14 articles for OCD, 1 for an OCD-related disorder (ie, hoarding disorder), 2 for PTSD, and 2 for anxiety disorders. In the studies involving OCD patients, tDCS was targeted to either the dorsolateral prefrontal cortex or the orbitofrontal cortex or the pre–supplementary motor area and induced a clear reduction of obsessive-compulsive symptoms. However, the lack of sham control groups and the great diversity in sample selection and tDCS protocols among studies prevent us from generalizing these results. In the studies involving PTSD and anxiety disorders patients, tDCS was applied over the dorsolateral prefrontal cortex and reduced symptoms, but the number of treated patients is too little to draw any conclusion on efficacy. However, these reports highlighted the importance of combining tDCS with different procedures, including computerized tasks and behavioral paradigms. In conclusion, even in its infancy, the use of tDCS for the treatment of OCD, PTSD, and anxiety disorders does show promise and deserves extensive research effort.